Mindfulness Apps and Student Mental Health: Digital Interventions for Reducing Academic Stress - Maria Clara Reyes; Luis Santos; Josefa Flores; Fauzi Aldina (Yayasan Adra Karima Hubbi, 2025)
Background. Academic stress has become a persistent mental health concern among students due to increasing academic demands and performance pressure. Digital mental health interventions, particularly mindfulness applications, have gained attention as accessible tools for stress management, yet empirical evidence focusing on academic stress remains limited. Purpose. This study aims to examine the relationship between mindfulness app use and student mental health, with specific attention to the reduction of academic stress in educational settings. Method. The study employs a quantitative correlational design supported by descriptive case analysis. Data were collected from students using standardized questionnaires measuring mindfulness app usage, academic stress, and mental well-being. Results. The findings reveal a significant negative correlation between mindfulness app use and academic stress, along with a positive relationship between app use and mental well-being. Consistent engagement with mindfulness apps was associated with lower stress levels and improved emotional regulation. Conclusion. The study concludes that mindfulness apps function as effective digital interventions for reducing academic stress when used consistently. The novelty of this research lies in emphasizing usage consistency as a key determinant of effectiveness and in integrating quantitative and contextual evidence to explain how digital mindfulness interventions support student mental health.